THE MECHANISM OF MARKETING THINKING IN EFECTIVE BUSINESS - Чернявська, Тетяна Павлівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
In the article describes a theoretical and methodological investigate of marketing aspect of business activity on the example of domestic managers of a manufacturing commercial enterprise. The purpose of the article is to reveal the specific features of marketing thinking as psychological factors of effective business activity, such as: search thinking style and focus on actual customer needs; development of a mechanism of marketing thinking of personality in the context of a business environment. For the diagnostic investigation the author used: survey (interview-conversation according to a certain plan), free interview without strict details on the general program; self-assessment profiles, expert evaluation by top managers of the effectiveness of mid-level managers; introspective survey with further structural survey and detailed record of answers. The mechanism scheme of marketing thinking in effective business is developed and presented. The basis of the mechanism of marketing thinking of managers is the feeling of the need for change, the search for and finding new economic opportunities and resources associated with this feeling. From these opportunities, the subject chooses viable and optimal in the context of a specific business environment and develops several alternative solutions to the actual needs (actual benefits, values) of customers. The theoretical significance of the investigate lies in the development and justification of the possibility of increasing the effectiveness of business activities of managers by forming and developing their marketing thinking and entrepreneurial value orientations using inside the company training, namely social psychological training. The actual direction of further research is the development of: methods aimed at the formation of significant specific associations of components of marketing thinking and value orientations that optimize the business activities of managers, businessmen; development, implementation and development in the direction of creative and search corrective-development program of marketing thinking of managers, which will promote the development of their effective business activity